Excitonic processes in atomically-thin MoSe2/MoS2 vertical heterostructures. (27th June 2018) - Carozo, Victor; Fujisawa, Kazunori; Rao, Rahul; Kahn, Ethan; Cunha, Jose Renato; Zhang, Tianyi; Rubin, Daniel; Salazar, Mario Flores; de Luna Bugallo, Andrés; Kar, Swastik; Terrones, Mauricio
Abstract: The relaxation of complex excitons in 2D materials is a topic of immense interest, due to their relevance in various optical and optoelectronic applications. In particular, relatively little is known regarding the dynamics in directly-synthesized heterostructures of dissimilar 2D materials, which are prototype architectures for atomically-thin optoelectronic devices. In this work, we have investigated vertical heterostructures (VH) of as-grown MoSe2 on MoS2 . Specifically, we studied spatially-resolved photoluminescence at room and low temperatures, thermal stability and power dependence through photoluminescence spectroscopy combined with atomically resolved scanning transmission electron microscopy (STEM). The VH structure forms a Moiré pattern which was observed by high-resolution STEM imaging. At room temperature, we observed a tenfold suppression of the neutral exciton of MoSe2 in the VH area compared with individual MoSe2 layer, due to negative charge transfer from MoSe2 to MoS2 . As a result, trions were found in MoS2 . At low temperature, the intensity of the neutral exciton from the MoS2 in the VH area is suppressed. The thermal quenching of the neutral exciton at temperatures below 140 K is related to the trapping of the neutral excitons in mid-gap states induced by defects. These states are effective at trapping excitons to form bound excitons. Finally, using power dependence experiments, we identified three types of the excitonic complexes at 77 K besides the neutral exciton: trions, biexcitons and bound excitons.